â€œMENJALIN UKHUWAH MENUMBUHKAN GHIRAHâ€ KEPADA GURU YAYASAN NABEEHA ULYA DESA BLABAK KECAMATAN KANDAT KABUPATEN KEDIRI - Ema Nurzainul Hakimah (Jurnal Abdi Masyarakat, 2019)
Teachers "digugu and imitated" wherever they are are personal figures with noble character and it must be realized by the actors as the main figures in the school environment. This main role is often not realized by teachers either as professionals or as part of an organization. Based on these preliminary observations, a training with the theme "Establishing Ukhuwah Fostering Ghirah" to the teachers of the Nabeeha Ulya Foundation, with the aim of fostering empathy and loyalty to the institutions where they serve both the MI Al Ikhlash work unit and Khodijah PAUD. The stages carried out in this activity began from the initial survey of two institutions under the Nabeeha Ulya Foundation, identification of various problems in the organization, training with resource persons, simulations, assistance and evaluation. The results of this training have an impact on increasing understanding of individual behavior in organizations and openness to convey understanding of the vision and mission of each institution.